Teaching students to collaborate with communities: expanding engineering education to create a sustainable future. Issue 1 (2nd January 2023) - Hirsch, Jennifer; Yow, Ruth; Wu, Yi-Chin Sarah
Abstract : Engineers are crucial to solving the world's most pressing challenges, but they cannot do it alone. Creating new and more just systems that support people and planet requires that engineers learn to engage with diverse stakeholders as equal partners. This article shares how the Serve-Learn-Sustain (SLS) initiative at the Georgia Institute of Technology has been introducing new approaches to problem-solving into engineering and technology-focused education to better prepare students to address the sustainability challenges of our moment, in collaboration with community partners, especially those from historically marginalized communities of color. To do this, SLS focuses on de-centering academic expertise and positioning community partners as experts, innovators, and co-educators. The activities and impacts described here, including course-based collaborations with community partners and co-curricular social innovation programs, have implications for other higher education institutions that recognize the importance of partnering with communities to prepare students to use their education to effect change.